Penerapan Teknik Expressive Therapy dalam Menghadapi Problematic Social Media Use - Ramadhani, Annisa Fortuna; Karneli, Yeni (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
Today, many people experience problematic social media use. Problematic social media use is a term that shows the negative impact of social media use. Namely, when someone begins to feel dependent on the use of social media. This happens when someone feels social media is their need. Using expressive therapy techniques aims to help clients express feelings or problems they face, both verbally and non-verbally. This study aims to collaborate on the theoretical basis and practice of counseling as an alternative in dealing with problematic social media use problems. The research method used is the library research method. The data analysis technique used is content analysis. Namely, to maintain accuracy in the assessment and misinformation in data analysis, it is necessary to check between libraries and re-read the literature. The results of this study are the elaboration of the theoretical and practical foundation of counseling, including: 1) Problematic social media use, 2) Definition of expressive therapy techniques, 3) Characteristics of expressive therapy techniques, 3) Forms of application of expressive therapy techniques, and 4) The role of expressive therapy techniques in dealing with problematic social media use.